Service To The Community Of The Covid 19 Disaster (PKM-BC19) In Limbukan Kelurahan, Selatan Payakumbuh District, Payakumbuh City - Yenrina, Rina; Guci, Krisna (Andalasian International Journal of Social and Entrepreneurial Development, 2021)
Community Service for the Covid-19 Disaster (PKM-BC19) is the theme Community Service Program (KKN) thematic Faculty of Agricultural Technology, Andalas University.Service activities are more focused on Covid-19 volunteers who are tasked with educating the public. Students accompanied by lecturers carry out activities individually at their respective residences and occasionally come downdirectly to residents while still adhering to health protocols.The location for the implementation of student KKN is in Limbukan Village, South Payakumbuh District, Payakumbuh City. The work program carried out during KKN includes main activities, supporting activities and multimedia activities. The main activities are activities related to Covid-19. Supporting activities are activities related to economic, environmental, social improvement and public education.Additional activities or multimedia activities that students do are making educational videos which are then uploaded to social media such as Instagram, WhatsApp and Youtube